The consumer in the Soviet economy - Hanson, Philip (London ; Melbourne : Macmillan, 1968)
This is a study of Soviet personal consumption levels and of the influence of consumer demand in the Soviet economy. It tries to establish what the effects of Soviet development priorities on consumption have been.
Includes bibliographical references and index.
ne 24/01/2019
Loans
Keywords: Consumption (Economics).; Cost and standard of living